2015
DOI: 10.1186/s13045-015-0203-8
|View full text |Cite|
|
Sign up to set email alerts
|

NLK functions to maintain proliferation and stemness of NSCLC and is a target of metformin

Abstract: ObjectiveNemo-like kinase (NLK) is an evolutionarily conserved serine/threonine kinase that regulates the activity of a wide range of signal transduction pathways. Metformin, an oral antidiabetic drug, is used for cancer prevention. However, the significance and underlying mechanism of NLK and metformin in oncogenesis has not been fully elucidated. Here, we investigate a novel role of NLK and metformin in human non-small cell lung cancer (NSCLC).Materials and methodsNLK expression was analyzed in 121 NSCLCs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…Besides, NLK is reported to regulate various signalling pathways, such as pro‐tumour Wnt,36 Notch37 and mTOR signalling38 as well as anti‐tumour Hippo signalling 39. This might be the reason why NLK exerts diverse functions during different cancers 23,40,41. However, sometimes there are contradictions about NLK function when in different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, NLK is reported to regulate various signalling pathways, such as pro‐tumour Wnt,36 Notch37 and mTOR signalling38 as well as anti‐tumour Hippo signalling 39. This might be the reason why NLK exerts diverse functions during different cancers 23,40,41. However, sometimes there are contradictions about NLK function when in different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…IHC was performed in order to determine RBM47 expression levels and distribution patterns of 175 pairs of NSCLC tissues. IHC was performed in accordance with previous studies (30,31). Tissue samples were cut into 4-µm-thick sections and incubated in Rabbit polyclonal RBM7 antibody (1:500; cat.…”
Section: Methodsmentioning
confidence: 99%
“…The intensity of immunoreactivity was scored as follows: 0, negative; 1, weak; 2, intermediate and 3, strong. The samples were grouped according to the sum of the immunoreactivity score as follows: 0, negative; 1-2, weak; 3, moderate and 4-6, strong (31). Final immunoreactivity scores >0 were considered positive, and those at 0 were considered negative.…”
Section: Evaluation Of Ihc Rbm47-positive Cells Displayed Brownishmentioning
confidence: 99%
“…against LTs have been published. In vivo studies have been performed to explore and extend observed drug efficacy against LTs in a more physiological setting [87,88]. Several studies have tried combination therapy approaches in LTs setting to develop effective drug combinations to alleviate therapy resistance-related concerns and improve efficacy of existing cancer drugs [68,[89][90][91][92].…”
Section: Floating Tumorspheresmentioning
confidence: 99%